Role of Surgery in the Management of Liver Metastases From Gastrointestinal Stromal Tumors - Xue, Anwei; Gao, Xiaodong; He, Yifeng; Shu, Ping; Huang, Xiaowu; Sun, Jianyi; Lu, Jiangshen; Hou, Yingyong; Fang, Yong; Shen, Kuntang (Frontiers in Oncology, 2022)
Background: The clinical benefit of hepatectomy in patients with liver metastases from gastrointestinal stromal tumors (GIST) has not been well defined in this era of tyrosine kinase inhibitor (TKI). Our study aims to demonstrate the survival advantage of adding hepatectomy in patients with GIST liver metastases. Methods: Information on patients with metastatic GIST treated or consulted between January 2006 and December 2018 was retrieved. Patients without extrahepatic metastases were included and classified into the surgical (S group) and non-surgical (NS group). Clinicopathological features were compared and their association with survival was assessed. Results: A total of 119 patients were included in this retrospective analysis, 62 in the S group and 59 in the NS group. Comparison of clinicopathological features showed that a markedly higher proportion of patients in the S group had ≤3 hepatic lesions (79.0% vs. 29.8%, p＜0.001). After a median follow-up duration of 56 months, patients in the S group had significantly better progression-free survival (PFS) and marginally improved overall survival (OS) than those in the NS group (3y PFS:86.2% vs. 64.6%, p=0.002; 5y OS: 91.5% vs. 78.3%, p=0.083). After propensity score matching, multivariate analysis identified hepatectomy as the only significant prognostic factor for PFS while age, hepatectomy and max tumor diameter were significant predictor for OS. Conclusions: Addition of hepatectomy provided longer disease control in patients with metastatic GIST confined to the liver. Upfront hepatectomy followed by imatinib therapy is worthwhile trying in patients with single and easily removable lesions.